A novel pulse-adaption flow control method for a turbocharger turbine: Elastically restrained guide vane. (July 2020) - Wang, Zhihui; Ma, Chaochen; Zhang, Hang; Zhu, Fei
A turbocharger is a key enabler for energy conservation in an internal combustion engine. The turbine in a turbocharger is fed by highly pulsating gas flow due to the reciprocating engine, resulting in significant deterioration of the turbocharger performance. To solve this problem, a novel pulse-optimized regulation mechanism named 'elastically restrained guide vane' for a novel variable geometry turbocharger is proposed in this paper. The new mechanism regulates the instantaneous flow angle at turbine inlet due to guide vane's self-adaptive rotation under interactions of the elastic force by elastically restrained guide vane and the aerodynamic force from flowing gas, which is different from the traditional variable geometry turbocharger that is achieved by an active control system (e.g. actuator). To investigate the effectiveness of the novel method, a double-passage computational fluid dynamics model is built in ANSYS CFX software combined with a fluid-structure interaction method. The results demonstrate that the pulse-adaptive regulation method can effectively adjust the nozzle opening according to the different pulsating pressures at turbine inlet. Subsequently, based on the calibrated models, the numerical simulation concentrates on the potential gain in turbine eventual power output and the exhaust energy recover as well as the corresponding effects on efficiency as a result of operating the turbocharger in its elastically restrained guide vane mode compared to its operation as a conventional variable geometry turbocharger.